System of observation for kinesic communication of the physical activity instructor for the elderly – (SOCIN-Elderly): a proposal - Belmonte, Luiz Augusto (2017)
Goldin-Meadow (2004) emphasizes the importance that gestures can assume at the level of the visual component of verbal discourse, where a particular gesture (meaning: movements performed essentially with arms and hands) may suggest a certain thought that often It can´t be expressed in words, thus having an important impact on learning activities. Thus, the study of non-verbal communication of physical activity instructors may be relevant, since they spend a great deal of time in kinetic communication, in the context of group classes. The SOCIN-Elderly aims to analyze variables associated with the kinetic communication of physical activity instructors for the elderly, whose representativeness may allow a multidimensional analysis of the non-verbal communication intervention profile of instructors, through a systematic and reliable observation of the events that occurred. For the development of this system, it will start with the adaptation of the Observational System of Communication (SOCIN), which is part of the Paraverbal Communication Observation System (SOCOP) developed by Balcells (2009) for the teaching context of the physical education, and of the System of Observation of the Communication of Kinetic of the Instructor of Fitness (SOCI-Fitness). The system will consist of 4 dimensions (function, morphology, situation, adapters) composed of 22 categories of analysis of the nonverbal communication of the instructor. The dimensions and categories of the system will be categorized to ensure its exclusivity and completeness, which will make it possible to eliminate certain ambiguities existing in the categorization process, simplifying its interpretation later and conferring objectivity and rigor to the coding process. Concerning the recording method, the sessions will be observed in an integral way, being recorded an occurrence whenever the instructor addresses the practitioner (s) with the intention of communicating in a non-verbal way, through a gesture with and without communicative intention. Concerning registration conventions, video recordings (picture and sound) will be carried out with the use of a digital camera, and later its content will be transferred to the hard disk of a computer. For the visualization and registration of occurrences, it will be used the program LINCE. Once the data is collected through video recording, participants will be informed in advance and will have to give their informed consent in writing, and all ethical criteria that protect the participant will be met. The final results should allow better kinetic communication with benefits for physical instructors and other professionals.